Modelling and application of a new method to measure the non-thermal electron current in the edge of magnetically confined plasma. (20th October 2021) - Liu, S.C.; Liang, Y.; Zhang, H.X.; Yan, N.; Liao, L.; Zhang, X.X.; Liu, X.J.; Wei, W.Y.; Zhao, N.; Chen, L.; Chen, R.; Hu, G.H.; et al.
Abstract: The non-thermal electrons could form considerable current in the edge plasma of tokamak and stellarator. A new method, named directional electron probe (DEP), is proposed to measure the edge non-thermal electron current in magnetically confined plasma. The DEP consists of two opposite channels whose connection line aligns with the local magnetic field line. Each channel has a hole with small radial width and enough thickness to block high energy ions due to their large Larmor radii, and at the end of the hole the collector is biased to positive voltage to repel low energy ions. In this way, the collected current of DEP is mainly contributed by electrons. A particle orbit simulation is performed based on the Boris algorithm, which demonstrates the validity and rationality of the DEP. According to the simulation, the ion collection probability is quite small if compared with the electron collection probability, consequently the collected current is mainly contributed by electrons. The collected currents of thermal electrons under Maxwell–Boltzmann distribution from both channels are almost equal, and the net current is driven by non-thermal electrons. A radial array of DEP has been successfully applied to the scrape-off layer (SOL) non-thermal electron current measurement in EAST. The amplitude and structure of the non-thermal electron current are observed during the lower hybrid wave heating phase. The experimental SOL net current is compared with the simulated net current from a rough estimation, revealing the same radial structure of SOL current and demonstrating the validity of DEP.